'Giving the gift of lots of time and attention'. (2nd May 2019) - Solly, Kathryn
Abstract : Kathryn Solly is immensely enjoying being a grandparent, not least because it provides a second chance to understand children's development and uniqueness. Here she describes Emilia and Jack's progress.